Validity and Psychometric Properties of the Early Development Instrument in Canada, Australia, United States, and Jamaica - Janus, M.; Brinkman, Sally; Duku, E. (Springer Netherlands, 2011)
Validity and Psychometric Properties of the Early Development Instrument in Canada, Australia, United States, and JamaicaAuthor(s): Janus, M (Janus, Magdalena)1; Brinkman, SA (Brinkman, Sally A.)2,3,4; Duku, EK (Duku, Eric K.)1Source: SOCIAL INDICATORS RESEARCH Volume: 103 Issue: 2 Pages: 283-297 DOI: 10.1007/s11205-011-9846-1 Published: SEP 2011Times Cited: 0 (from Web of Science)Cited References: 44 [ view related records ] Citation MapCitation Map Abstract: There is an increasing support from international organizations and the research community for stepping beyond infant or child mortality as the most common child level social indicator and progressing towards an international measure of child development. The Early Development Instrument (EDI) is a teacher-completed measure of children's developmental health at school entry, which to date has been used in more than a dozen countries. The EDI includes five developmental domains (Physical Health and Well-being, Social Competence, Emotional Maturity, Language and Cognitive Development and Communication Skills and General Knowledge) and 16 subdomains. This paper examines the EDI's psychometric properties in four English-speaking countries (Canada, Australia, United States and Jamaica) by evaluating both the internal consistency and factor structures, as well as exploring the association between the EDI's Language and Cognitive Development Domain and a direct assessment of children's receptive vocabulary (Peabody Picture Vocabulary Test, PPVT). Overall, the factor loadings and internal consistencies of domains and subdomains were similar across the countries. The comparisons of the Language and Cognitive Development Domain with the PPVT showed high specificity and low sensitivity. The results of this paper indicate that the EDI, a measure of children's developmental status at school entry, demonstrates similar psychometric properties in a number of countries, thus building the evidence for the instrument to be added to the limited array of internationally comparable child social indicators.Document Type: ArticleLanguage: EnglishAuthor Keywords: Child development; Social indicators; International studies; Population-level outcomesKeyWords Plus: DIFFICULTIES QUESTIONNAIRE; CULTURAL-ADAPTATION; STRENGTHS; CHILDREN; QUALITY; EQUIVALENCE; TRANSLATION; MODELReprint Address: Janus, M (reprint author), McMaster Univ, Dept Psychiat & Behav Neurosci, Offord Ctr Child Studies, Patterson Bldg,1200 Main St W, Hamilton, ON L8N 3Z5, CanadaAddresses:1. McMaster Univ, Dept Psychiat & Behav Neurosci, Offord Ctr Child Studies, Hamilton, ON L8N 3Z5, Canada2. Curtin Univ, Ctr Dev Hlth, Subiaco, WA 6008, Australia3. Univ Western Australia, Telethon Inst Child Hlth Res, Subiaco, WA 6008, Australia4. Univ Adelaide, Australian Inst Social Res, Adelaide, SA 5005, AustraliaE-mail Address: janusm@mcmaster.caPublisher: SPRINGER, VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDSWeb of Science Category: Social Sciences, Interdisciplinary; SociologySubject Category: Social Sciences - Other Topics; SociologyIDS Number: 800WDISSN: 0303-8300 Times Cited: 0This article has been cited 0 times in Web of Knowledge.Receive an e-mail when someone cites this recordRelated Records:Find similar Web of Knowledge records based on shared references.[ view related records ]Cited References: 44View the bibliography of this record (from Web of ScienceSM).Citation MapCitation MapAdditional information View the journal's Table of Contents (in Current Contents Connect®) View the journal's impact factor (in Journal Citation Reports®)View this record in other databases: View citation data (in Web of ScienceSM) View most recent data (in Current Contents Connect®)Suggest a correctionIf you would like to improve the quality of the data in this record, please suggest a correction. << Back to results list Previous Record (inactive) Record 1 of 74 Next Record Record from Web of ScienceSM Output Record Step 1:Authors, Title, Source plus AbstractFull Record plus Cited References Step 2: [How do I export to bibliographic management software?]Save the selected records to My EndNote Web library Save to: